Factors Related to Health Worker Performance: Systematic Review - Ainun Hafilda, Shafira; Misnaniarti, Misnaniarti; Syakurah, Rizma Adlia (Jurnal KESANS : Kesehatan dan Sains, 2025)
Health human resources have a major impact in increasing the competitiveness of health services. The performance of health workers is a consequene of the needs and demands of society to obtain high quality health services. This research aims to determine the factors related to the performance of health workers. This type of research is a systematic review which is carried out by collecting and accumulating research related to factors related to the performance of health workers. The keywords used for literature searches; "performance of health workers" and "performance of health workers". The literature sources used in the research come from online databases, namely Google Scholar and PubMed, and Elsevier. The results of this research are factors related to the performance of health workers consisting of education, training, work motivation, leadership, salary satisfaction, and work stress